Helminth infestation causing anaemia in pregnancy attending primary care clinic: a case report - Roop Kishore, Yashdev Atri; Shalihin, Mohd Shaiful Ehsan (Universiti Malaysia Sabah (UMS), 2024)
Anaemia in pregnancy is among the commonest medical disorders encountered antenatally. However, the condition has sometimes been overlooked and not corrected accordingly given wrong or unidentified exact causes. Helminth infestation, even though rare generally nowadays, is still an important cause that needs to be ruled out in case of anaemia. We reported a case of an antenatal woman who presented with unresolved anaemia. However, she benefited from the helminth infestation screening and was able to be treated well. Her condition tremendously improved after the eradication of the infection. This case highlighted that anaemia should always include stool for ova and cyst despite no convincing history towards the infection. The symptoms could be mild or even not recognised.